2021
DOI: 10.1016/j.omtn.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

circMELK promotes glioblastoma multiforme cell tumorigenesis through the miR-593/EphB2 axis

Abstract: A number of studies indicate that circular RNAs (circRNAs) play paramount roles in regulating the biological behavior of glioblastoma multiforme (GBM). In this study, we investigated the underlying mechanism of circMELK in GBM. Real-time PCRs were used to examine the expression of circMELK in glioma tissues and normal brain tissues (NBTs). Localization of circMELK in GBM cells was estimated by fluorescence in situ hybridization (FISH). Transwell migration and three-dimensional invasion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
(46 reference statements)
0
27
0
Order By: Relevance
“…In glioblastoma multiforme (GBM), EphB2 overexpression correlated to poor overall survival in GBM patients. CircMELK could upregulate EphB2 expression by sponging miR-593, thereby promoting the proliferation, invasion, migration, and glioma stem cell (GSC) maintenance of GBM cells ( Zhou et al, 2021 ). Moreover, Qiu et al reported that EphB2 expression was upregulated in GBM cells under hypoxia and the stabilization of EPHB2 by hypoxia required the participation of hypoxia-inducible factor-2α (HIF-2α).…”
Section: Ephb2 In Various Human Tumorsmentioning
confidence: 99%
“…In glioblastoma multiforme (GBM), EphB2 overexpression correlated to poor overall survival in GBM patients. CircMELK could upregulate EphB2 expression by sponging miR-593, thereby promoting the proliferation, invasion, migration, and glioma stem cell (GSC) maintenance of GBM cells ( Zhou et al, 2021 ). Moreover, Qiu et al reported that EphB2 expression was upregulated in GBM cells under hypoxia and the stabilization of EPHB2 by hypoxia required the participation of hypoxia-inducible factor-2α (HIF-2α).…”
Section: Ephb2 In Various Human Tumorsmentioning
confidence: 99%
“…Mucin (MUC) acts as an inducer to activate various signaling pathways that also contribute to EMT ( Ponnusamy et al, 2013 ). We found that among the circRNAs involved in GBM, circ-MMP9( Wang et al, 2018b ), hsa_circ_0067934 ( Xin et al, 2019 ), hsa_circ_0001801 ( Chen et al, 2019 ), circ-PARP4 ( Zhou J. et al, 2021 ), circ-PITX1 ( Cao et al, 2021 ), hsa_circ_0006168 ( Wang T. et al, 2021 ), hsa_circ_0001588 ( Wang Q. et al, 2021 ) and circ-MELK ( Zhou F. et al, 2021 ) can regulate GBM invasion and metastasis by modulating the EMT process. Hsa_circ_0067934 ( Xin et al, 2019 ), circ-EPB41L5 ( Lv et al, 2020 ) and circ-ABCC3( Zhang and Xu, 2021 ) can participate in the invasion and metastasis of GBM by regulating the PI3K/Akt/mtor signaling pathway.…”
Section: Biological Function and Molecular Mechanism Of Circular Rnas In Glioblastomamentioning
confidence: 99%
“…CircRNAs have vital roles in the invasion and metastasis of GBM. Hsa_circ_0008344 ( Zhou et al, 2018 ), circ-MMP9( Wang et al, 2018b ), hsa_circ_0029426 ( Zhang G. et al, 2019 ), hsa_circ_0074027 ( Qian et al, 2019 ), hsa_circ_0067934 ( Xin et al, 2019 ), circ-FOXO3 ( Zhang S. et al, 2019 ), hsa_circ_0001801 ( Chen et al, 2019 ), circ-EPB41L5 ( Lv et al, 2020 ), circ-ENTPD7 ( Zhu et al, 2020 ), hsa_circ_0043278 ( Wu et al, 2020 ), circ-PARP4 ( Zhou J. et al, 2021 ), circ-SMARCA5 ( Barbagallo et al, 2021 ), circ-PITX1 ( Cao et al, 2021 ), circ-ABCC3( Zhang and Xu, 2021 ), hsa_circ_0006168 ( Wang T. et al, 2021 ), hsa_circ_0001588 ( Wang Q. et al, 2021 ), circ-MELK ( Zhou F. et al, 2021 ), circ-FLN1 ( Sun et al, 2021 ), circ-LGMN( Chen B. et al, 2021 ), circ-NT5E ( Wang et al, 2018a ), hsa_circ_0001946 ( Li and Diao, 2019 ) and circ-MTO1 ( Zhang X. et al, 2019 ) are involved in the regulation of GBM invasion and metastasis ( Table 2 ).…”
Section: Biological Function and Molecular Mechanism Of Circular Rnas In Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Its overexpression can rescue the inhibition regulation of the oncogenic proteins SOX9 and ITGA5 by miR-145-5p and miR-330-5p in GSCs, respectively, resulting in increased proliferation, self-renewal and stemness of GSCs ( 67 ). Simliar to circPTN, circMELK and circPARP4 regulate GBM EMT and stemness of GSCs through upregulating oncogenic protein EphB2 and FUT4 by acting as sponges for miR-593 and miR-125a-5p, respectively ( 66 , 150 ).…”
Section: Mechanisms In Glioma Progressionmentioning
confidence: 99%